Methylammonium Polyiodides in Perovskite Photovoltaics: From Fundamentals to Applications - Petrov, Andrey A.; Tarasov, Alexey B. (Frontiers in Chemistry, 2020)
Discovered in 2017, methylammonium polyiodides were proposed as a facile precursor for synthesis of hybrid perovskites by means of their interaction with metallic lead, which initiated further active exploration of their potential applications. Investigation of their unusual properties such as liquid state, unprecedented phase diversity and high reactivity revealed that methylammonium polyiodides are the first representatives of a new class of compounds – reactive polyhalide melts (RPM). In this review, we summarize the reported data on the unique properties of these compounds, discuss their potential for fabrication of hybrid perovskite films and describe the role of polyhalides in degradation of perovskite solar cells.